Recent Goldstone radar observations of selected near-Earth asteroids less than 140 m in diameter. Issue Volume 10:Issue S318(2015) (1st March 2016) - Brozović, Marina; Benner, Lance A. M.; Busch, Michael W.; Giorgini, Jon D.; Slade, Martin A.; Lawrence, Kenneth J.
Abstract: Radar observations are a powerful technique to study near-Earth asteroids (NEAs). Goldstone's 3.75 m resolution capability is invaluable when attempting to image NEAs with diameters smaller than 140 m. The small NEAs are a very diverse population in which we continue to discover unusual objects.